Fucoxanthin Abrogates Ionizing Radiation-Induced Inflammatory Responses by Modulating Sirtuin 1 in Macrophages - Hyunju Kang; Seon-Chil Kim; Youngkee Oh (Marine Drugs, 2023)
Ionizing radiation (IR) triggers an overproduction of reactive oxygen species (ROS), disrupting the normal function of both immune and metabolic systems, leading to inflammation and metabolic disturbances. To address the pressing requirement for protection against IR, fucoxanthin (FX), a naturally occurring compound extracted from algae, was utilized as an efficient radioprotective agent in macrophages. In this study, we cultured murine RAW 264.7 macrophages and treated them with FX, along with agents influencing the activity of sirtuin 1 (SIRT1) and estrogen receptor α (ERα), to investigate their impact on IR-induced cellular responses. FX significantly attenuated IR-induced upregulation of pro-inflammatory genes (Il1b, Tnf, and Ccl2) and inhibited macrophage polarization toward the pro-inflammatory M1 phenotype. Additionally, FX regulated IR-induced metabolic genes mediating glycolysis and mitochondrial biogenesis. The ability of FX to mitigate IR-induced inflammation and glycolysis was ascribed to the expression and activity of SIRT1 and ERα in macrophages. This study not only uncovers the underlying mechanisms of FX's radioprotective properties but also highlights its potential as a protective agent against the detrimental effects of IR, thus offering new opportunities for enhancing radiation protection in the future.